The Impact of Past Behavior, Attitude towards Counterfeit, Self Characteristic, and Purchase Intention of Original Crocs towards Consumer Purchase Intention of Counterfeit Crocs - Vely Tannia Lianto (iBuss Management, 2015)
This research is conducted to reveal the impact of past behavior, attitudes toward counterfeit, self-characteristic, and purchase intention of original Crocs towards the purchase intention of counterfeit Crocs. This problem needs to be analyzed because of the widespread of counterfeit in Indonesia which causes economical loss for the country. Data collection is done through simple random sampling method. There are 140 respondents. The analysis in the research is done through multiple linear regressions to describe the relationship between the independent and dependent variables. All the variables are also tested using blue classic assumption test, F-test, and t-test. The finding shows that the independent variables simultaneously impact the consumer purchase intention of counterfeit Crocs.Keywords: Past Behavior, Attitudes toward Counterfeit, Self-Characteristic, Consumer Purchase Intention.